2021
DOI: 10.1186/s12883-021-02090-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features with anti fibroblast growth factor receptor 3 (FGFR3) antibody-related polyneuropathy: a retrospective study

Abstract: Background Despite its initial association with sensory neuropathies, anti-fibroblast growth factor receptor 3 (FGFR3) antibodies have been since reported with a broad range of neuropathies and clinical features. The aim of the study is to report the clinical and electro diagnostic findings in a cohort of patients with sensory or sensorimotor polyneuropathy and anti-FGFR3 antibodies. Methods We performed a retrospective chart review to assess the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…168,169 Antibodies binding to trisulfated heparin disaccharide (TS-HDS), 191,192 and the intracellular domain of the fibroblast growth factor receptor 3 (FGFR3) 193 have been detected in patients with apparently idiopathic sensory neuropathy, often with features of sensory neuronopathy, 193 including NLD-SFN. [170][171][172][173][174] It is still unclear whether these are autoantibodies playing a pathogenic role or are only biomarkers of a dysimmune process, and whether they can identify patients who would respond to immune intervention. 194 Finally, predispositions towards dysimmunity in some patients with idiopathic SFN is suggested by findings of minor abnormalities of immune and inflammatory biomarkers, 42,115,195 as also observed in NLD-SFN.…”
Section: Associated Conditionsmentioning
confidence: 99%
“…168,169 Antibodies binding to trisulfated heparin disaccharide (TS-HDS), 191,192 and the intracellular domain of the fibroblast growth factor receptor 3 (FGFR3) 193 have been detected in patients with apparently idiopathic sensory neuropathy, often with features of sensory neuronopathy, 193 including NLD-SFN. [170][171][172][173][174] It is still unclear whether these are autoantibodies playing a pathogenic role or are only biomarkers of a dysimmune process, and whether they can identify patients who would respond to immune intervention. 194 Finally, predispositions towards dysimmunity in some patients with idiopathic SFN is suggested by findings of minor abnormalities of immune and inflammatory biomarkers, 42,115,195 as also observed in NLD-SFN.…”
Section: Associated Conditionsmentioning
confidence: 99%
“…Abs recognizing the TK domain correspond to a more severe disease. Other studies have associated anti-FGFR3 Abs with a wider spectrum of neuropathy [72][73][74][75]. The method used for the Abs detection is certainly crucial for the specificity of the results [76].…”
Section: Antibodies In Idiopathic Sensory Neuronopathies and Sensory ...mentioning
confidence: 99%
“…It can be a manifestation of an underlying systemic disease, like sarcoidosis [11 ▪ ,12 ▪ ] or Sjögren syndrome [13 ▪ ,14 ▪ ]. In addition, various auto-antibodies have been linked to SFN, in the absence of systemic diseases [15 ▪ ,16 ▪▪ ,17 ▪▪ ]. Besides, postinfectious and postvaccination cases of SFN have been described, in which immune-mediated mechanisms are supposed to be causative [18 ▪ ,19 ▪ ,20 ▪ ,21 ▪ ,22 ▪ ,23 ▪ ,24 ▪ ,25 ▪ ,26 ▪ ].…”
Section: Immune-mediated Small Fiber Neuropathymentioning
confidence: 99%
“…Antibodies against FGFR3 were already linked to purely sensory-predominant neuropathies or neuronopathies. A recently conducted retrospective study, showed a broader clinical spectrum with involvement of both small and large fibers, sensory, and motor fibers, and the trigeminal nerves [15 ▪ ].…”
Section: Immune-mediated Small Fiber Neuropathymentioning
confidence: 99%